Macrophage exosomes as natural nanocarriers for protein delivery to inflamed brain. (October 2017) - Yuan, Dongfen; Zhao, Yuling; Banks, William A.; Bullock, Kristin M.; Haney, Matthew; Batrakova, Elena; Kabanov, Alexander V.
Abstract: Recent work has stimulated interest in the use of exosomes as nanocarriers for delivery of small drugs, RNAs, and proteins to the central nervous system (CNS). To overcome the blood-brain barrier (BBB), exosomes were modified with brain homing peptides that target brain endothelium but likely to increase immune response. Here for the first time we demonstrate that there is no need for such modification to penetrate the BBB in mammals. The naïve macrophage (Mϕ) exosomes can utilize, 1) on the one hand, the integrin lymphocyte function-associated antigen 1 (LFA-1) and intercellular adhesion molecule 1 (ICAM-1), and, 2) on the other hand, the carbohydrate-binding C-type lectin receptors, to interact with brain microvessel endothelial cells comprising the BBB. Notably, upregulation of ICAM-1, a common process in inflammation, promotes Mϕ exosomes uptake in the BBB cells. We further demonstrate in vivo that naïve Mϕ exosomes, after intravenous (IV) administration, cross the BBB and deliver a cargo protein, the brain derived neurotrophic factor (BDNF), to the brain. This delivery is enhanced in the presence of brain inflammation, a condition often present in CNS diseases. Taken together, the findings are of interest to basic science and possible use of Mϕ-derived exosomes as nanocarriers for brain delivery of therapeutic proteins to treat CNS diseases. Graphical abstract: